The Importance Of Digital Transformation In A Post-Pandemic World - Nosike, Rev Chukwunonso Joseph; Sandra, Nosike Oluchukwu; Uju, Nosike Cynthia (Development Policy and Management Review (DPMR), 2024)
In the wake of the global COVID-19 pandemic, the business landscape has undergone a profound transformation, necessitating a paradigm shift towards digitalization for sustained resilience and growth. This article explores the pivotal role of digital transformation in the post-pandemic world, encompassing technological innovation, organizational adaptation, and cultural evolution. Drawing on insights from scholarly sources, we delve into the accelerated digital trends triggered by the pandemic and the challenges faced by businesses in this transformative journey. The importance of digital transformation is underscored by its role in enhancing resilience, adapting to unforeseen challenges, improving customer experiences, and facilitating data-driven decision-making. While acknowledging the inherent challenges, a well-defined digital strategy emerges as a crucial determinant for success. As we navigate the evolving business landscape, this article aims to provide a comprehensive understanding of the significance of digital transformation in fostering organizational agility and long-term success.